Flooding Impact on Female Sex Workers and HIV and STI Prevention Services - เลิศพิริยสุวัฒน์ ชีวนันท์; ชินสงวนเกียรติ ยุพิน; มหรัตนวิโรจน์ วิภาดา; คล้ายนาค ฉวีวรรณ; ศรีสำรวล อัมพร; ไฝสุข ศิริพร; มากกุญชร จุฑามาศ; พงษ์สกุล พิชพันธ์; ใหม่สุวรรณ สุวนีย์ (Disease Control Journal, 2012)
Thailand faced with serious flood in many provinces during September 2011-December 2011. Bureau of AIDS, TB and STIs conducted a study to assess impact from flood among female sex workers (FSWs) and HIV and STI prevention services in order to use the results for developing a guideline to prepare comprehensive prevention services for the floods that may happen again in the future. Design of the study was cross sectional. Data were collected in 5 flooded-provinces, namely Nakorn Sawan, Lopburi, Ayutthaya, Nonthaburi and Bangkok, during December 2011-January 2012 which was around a month after flood. In order to gather qualitative data, focus group discussion was conducted among FSWs, and in-depth interview was applied among STI service providers and HIV counselors and NGO representatives. Samples were selected purposively. Data were analyzed using a content analysis method. Thirty-nine FSWs attended focus group discussions. Eleven health providers and 6 NGO representatives were interviewed. Impact from flood included closing of several sex establishments. Most of those continued open sex establishments report to have declined number of clients due to inconvenient travelling. However, sex establishments located in non¬flood area reported increasing number of clients. It is noted that, during flood period, some SWs moved to other provinces or new establishments and some direct SWs transformed to work as freelance. Most of SWs answered that they had sufficient condoms and used condoms regularly. Some NGOs couldn’t run their activities. One condom inventory of public health service was damaged. STI clinics were still capable to provide service in all provinces but number of clients was remarkably reduced. There was a report of increased gonorrhea incidence after flood in one province. In flooding situation, there is still a need to support condoms for SW in all sex establishments which can carry on their service, both in areas with and without flood. To effectively enhance HIV and STI prevention, condom should be made widely available and accessible to the public. In addition, mobile STI clinic service or referral system of patient may be necessary in areas with inconvenient transportation.